Analysis Of Ethnoscience-Based Problem-Based Learning (PBL) Models At The Elementary School Level: Bibliometric Analysis On Selected Journals In 2019-2025 - Damayanti, Lilis; Tri Joko Raharjo; Bambang Subali; Ellianawati Ellianawati (Universitas Negeri Semarang, 2024)
This study examines trends, contributions, and research directions related to ethnoscience-based Problem-Based Learning (PBL) models at the elementary school level during the 2019-2025. This study used a systematic literature review method with the PRISMA approach to select and analyze relevant scientific articles. Articles that met the inclusion criteria were analyzed using VOSviewer to map bibliometric visualizations, including keyword networks, authors, and research topic trends. The results showed that integrating ethnoscience in the PBL model consistently improved elementary school students' critical thinking skills, understanding of science concepts, and respect for local culture. In addition, this approach is also considered effective in increasing students' active involvement in the contextualized problem-based learning process. Research trends show a significant increase in ethnoscience approaches since 2019, especially in IPAS and science learning. VOSviewer analysis showed dominant keywords such as “ethnoscience,” “critical thinking,” and “basic education” interconnected in authorship and topic networks. This research confirms the importance of learning approaches that combine local wisdom with innovative methods such as PBL. This article recommends the need for further research that develops local culture-based learning models collaboratively between educators, communities, and education stakeholders.